PENINGKATAN HASIL DAN MINAT BELAJAR SISWA MELALUI MODEL PEMBELAJARAN VISUAL AUDITORI KINESTETIK (VAK) PADA MATERI CAHAYA KELAS V SDN SONDAKAN No.11 - Anisa Amalia; Kusuma Ardhani; Meilia Wulandari; Meggy Novitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to improve the learning outcomes and interest of fifth grade students at SDN Sondakan in light material, through the application of the Visual, Auditory, Kinesthetic (VAK) learning model. This research is Classroom Action Research (PTK) which was carried out in two cycles. The research subjects were 27 fifth grade students at Sondakan Elementary School. Data collection is carried out through observation, tests and documentation. The research results show that the application of the VAK model can improve student learning outcomes significantly. In the pre-cycle, only 35% of students achieved the Learning Goal Achievement Criteria (KKTP). After implementing the VAK model, the percentage of completion increased to 73% in cycle I and reached 92% in cycle II. Apart from that, students' interest in learning has also increased, which can be seen from four indicators. The overall average student interest in learning increased from the fairly high category in cycle I to high in cycle II. Thus, the application of the VAK learning model has proven to be effective in improving student learning outcomes and interest.